Impact of DLC Coating Deposition on the Fatigue Strength of Al-7075-T6 Aluminum Alloy (Journal of Material Science and Technology Research, 2023)
Abstract: Al-7075 has interesting mechanical properties but is susceptible to corrosion. Physical Vapor Deposition (PVD) of coatings results in good corrosion resistance and compressive stresses of the order of 1 GPa on the surface of metallic components. However, the impact of PVD films on the strength of Al-7075-T6 is uncertain. This paper provides a summary of the findings of the Authors’ research group in recent years on the fatigue behavior of Al-7075-T6 with and without PVD Diamond-like Carbon (DLC) coating. The results indicated that DLC-coated specimens have lower fatigue strength than uncoated specimens for lives up to about 10000000 cycles. The failure mechanism was determined by observation of the fracture surfaces of the failed specimens. The stress analysis performed confirms the experimental observation, with crack nucleation expected below the surface of coated specimens, where the highest tensile stresses occur during fatigue loading.